Analisis Waktu Penyediaan Dokumen Rekam Medis Rawat Jalan Menurut Model 5M di RSUD Ungaran - Hervina Gustian Susilo; Anton Kristijono; Niko Tesni Saputro (Indonesian of Health Information Management Journal (INOHIM), 2022)
AbstractThe time for providing outpatient medical record documents based on Permenkes No.129, 2008 is 10 minutes starting from the patient registering until the patient's medical record document is provided at the polyclinic. In a preliminary study conducted on 10 medical record documents, there were 7 (70%) whose time of provision of medical record documents was not following minimum service standards. If the time of provision of medical record documents is not improved, it will have an impact on the quality of service and patient satisfaction. The type of research used is descriptive quantitative research with a cross-sectional approach. The population is the number of outpatient visits totaling 85,727 from 13 existing polyclinics. Determination of the sample size using the Slovin formula obtained 100 medical record documents. Determination of samples from 13 polyclinics proportionally. Methods of data collection by observation and interviews. The results of the study showed that the average time for providing medical record documents was 19.94 minutes, not following the established minimum service standards and standard operating procedures. Factors affecting the delay in providing outpatient medical record documents from the 5M models were found to be 2M that had an effect, namely human factors and methods. Human resources in the filling department are only 4 officers (57.14%) of 7 officers who have a diploma education background of three medical records and only 2 officers (28.57%) who have received training in filling management. The method factor, standard operating procedures does not regulate and emphasizes ways, methods, or tools in providing medical record documents at the polyclinic on time according to minimum service standards. The implementation of the standard operating procedures has not yet been evaluated.Keywords: medical records, time providing, 5M AbstrakWaktu penyediaan dokumen rekam medis (DRM) pasien rawat jalan berdasarkan Permenkes No.129, 2008 adalah ≤10 menit dimulai dari pasien mendaftar sampai DRM pasien disediakan di poliklinik. Studi pendahuluan yang dilakukan dari 10 DRM terdapat 7 (70%) yang waktu penyediaan DRM tidak sesuai standar pelayanan minimum (SPM). Jika waktu penyediaan DRM sesuai data tersebut tidak dilakukan perbaikan, akan berdampak pada mutu pelayanan dan kepuasan pasien. Jenis penelitian yang digunakan adalah penelitian deskriptif kuantitatif dengan pendekatan cross sectional. Populasi adalah jumlah DRM kunjungan pasien rawat jalan berjumlah 85.727 dari 13 poliklinik yang ada. Penentuan besar sampel menggunakan rumus Slovin, didapatkan 100 DRM. Penentuan sampel dari 13 poliklinik secara proporsional. Metode pengumpulan data dengan observasi dan wawancara. Hasil penelitian rata-rata waktu penyediaan DRM adalah 19,94 menit, belum sesuai dengan SPM RS dan standar prosedur operasional (SPO) yang sudah ditetapkan. Faktor-faktor yang mempengaruhi keterlambatan penyediaan DRM rawat jalan dari 5M model ditemukan 2 M yang berpengaruh, yaitu faktor manusia dan metode. SDM di bagian filing baru 4 petugas (57,14%) dari 7 petugas yang mempunyai latar belakang pendidikan diploma tiga rekam medis dan hanya 2 petugas (28,57%) yang sudah mendapatkan pelatihan dalam pengelolaan filling. Faktor metode, SPO tidak mengatur dan menekankan cara, metode atau alat dalam menyediakan DRM di poliklinik dengan tepat waktu sesuai SPM. Pelaksanaan SPO juga belum dilakukan evaluasi.Kata Kunci: rekam medis, waktu penyediaan, 5M